1991
DOI: 10.1093/carcin/12.6.949
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific mutagenesis: retrospective and prospective

Abstract: IntroductionThe aim of this commentary is to discuss the underlying logic of experiments directed towards identifying specific DNA modifications responsible for the genetic effects of DNA damaging agents. Our aim is not to write a comprehensive review of the field, but rather to use examples from a single research area in which both of our laboratories participated, and thus to outline the general approaches used for site-specific mutagenesis. We also shall describe some of the advantages and the limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(7 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…1 Alkylation at nitrogen atoms on nucleobases has been shown to induce transversions, frameshift mutations, and small deletions. 2 Alkylation at oxygen atoms, albeit occurring to a lesser extent than N -alkylation, 3,4 primarily produces point mutations and is linked with the carcinogenic and mutagenic properties of many alkylating agents. 5 For larger alkylating agents, the reactivity of oxygen atoms in nucleobases differs, with the O 6 position of guanine being the most reactive, followed by the O 2 and O 4 positions of thymine, and then the O 2 position of cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…1 Alkylation at nitrogen atoms on nucleobases has been shown to induce transversions, frameshift mutations, and small deletions. 2 Alkylation at oxygen atoms, albeit occurring to a lesser extent than N -alkylation, 3,4 primarily produces point mutations and is linked with the carcinogenic and mutagenic properties of many alkylating agents. 5 For larger alkylating agents, the reactivity of oxygen atoms in nucleobases differs, with the O 6 position of guanine being the most reactive, followed by the O 2 and O 4 positions of thymine, and then the O 2 position of cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Quantitation of ethylated DNA adducts in human tissues could provide an approach to investigate the possible role of direct ethylating agents in human cancer. With this goal in mind, we previously developed a liquid chromatography-electrospray ionization-tandem mass spectrometry-selected reaction monitoring method for quantitation of 7-ethyl-Gua in human hepatic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, persistent miscoding of adducts compromises DNA repair systems resulting in accumulation of mutations in the genome. Multiple studies have indicated that cigarette smoke derived DNA adducts are responsible for miscoding mutations (9)(10)(11). Mutations in tumor suppressor genes or oncogenes enables uncontrolled growth and aid in development of cancer (12).…”
Section: Introductionmentioning
confidence: 99%